Screening of follicle-stimulating hormone dose-dependent expression genes - LIU Tian; CHEN Xiaoyu; ZHU Zhiwei; YU Fuxian; HUANG Jing; JIA Ruoxin; SHI Fangxiong; PAN Jianzhi (浙江大学学报. 农业与生命科学版)
To develop a new and effective method for detection of follicle-stimulating hormone (FSH) bioactivity, porcine follicular granulosa cells were used as experimental materials, and expression of genes in FSH-treated group (40 mIU/mL) and blank control group was compared by transcriptome sequencing to identify FSH-regulated candidate genes. Meanwhile, real-time fluorescent quantitative polymerase chain reaction was used to validate significantly upregulated genes after FSH treatments, and the porcine follicular granulosa cells were treated further by FSH dose gradients (0, 20, 40, 60, 80 and 100 mIU/mL). The results indicated that the expressions of OLR1, LHCGR, SCARA5 and S100A12 increased in a FSH dose-dependent manner. In addition, the expression of these four genes was determined in FSH dose gradients (0, 1, 3, 9, 27, 81, 243 and 729 mIU/mL), and the results showed that the correlation coefficient between the expression of LHCGR and dose gradient of FSH was close to 1 (R2=0.982) in the FSH dose range of 0-243 mIU/mL. In summary, LHCGR expression has a linear relationship with FSH dose, which may be helpful to develop a novel method for biological value detection of FSH.